"There is no joy in the family anymore": a mixed-methods study on the experience and impact of maternal mortality on families in Ghana - Emma R. Lawrence; Adu Appiah-Kubi; Hannah R. Lawrence; Maxine Y. Lui; Ruth Owusu-Antwi; Thomas Konney; Cheryl A. Moyer (BMC, 2022)
Abstract Background Maternal mortality has a multifaceted impact on families, especially in low- and middle-income countries, where rates of maternal mortality are high and resources can be lacking. The objective of this study was to explore the ways that maternal mortality influences the physical and emotional wellbeing, financial stability, and caregiving structure of families, and identifies sources of and gaps in support. Methods Our study used a mixed-methods design. All maternal mortalities in an 18-month period at a tertiary hospital in Ghana were identified using death certificates. Participants were 51 family members (either husbands or other heads of households) in families affected by maternal mortality. A questionnaire assessed demographic characteristics and changes in family health, income, and family structure. Two validated scales assessing psychological wellbeing were administered: the Patient Health Questionnaire-9 and the Inventory of Complicated Grief. Semi-structured interviews were conducted to assess impact on family wellbeing. Results Quantitative and qualitative results converged to highlight large, negative impacts of maternal mortality on four areas of family wellbeing: 1) mental health and emotional wellbeing; 2) physical health; 3) family structure; 4) financial stability and security. On the Patient Health Questionnaire-9, 54% (27/50) of participants reported elevated depressive symptoms, with 14% (7/50) of scores falling in the moderately severe or severe ranges. On the Inventory of Complicated Grief, 38% (19/50) exceeded the cutoff for significant impairment in functioning. Worsened family health was associated with greater complicated grief (b = 21.41, p = .004); there were no other significant predictors of depressive symptom severity or complicated grief. Effects on family health centered on concerns about the nutritional status and health of the surviving infant. Family structure was primarily affected by fracturing of the central family unit by sending children to live with relatives. Immense economic strain resulted from hospital bills, funeral expenses, and loss of income. The majority of participants received helpful support from their family (41/51, 80.4%), the community (32/51, 62.7%), and their religious institution (43/51, 84.3%); however, support often stopped soon after the death. Conclusions Maternal mortality has profound negative impacts on families in Ghana. Impacts are experienced by husbands and heads of households, as well as surviving children. Both immediate and sustained support is needed for families following a maternal death, especially mental health and financial support.